Do social conflicts with customers at work encroach upon our private lives? A diary study - Niessen, Cornelia; Volmer, Judith; Binnewies, Carmen; Sonnentag, Sabine (Journal of Occupational Health Psychology, 2012)
Social interactions at work can strongly influence people's well-being. Extending past research, we examined how social conflicts with customers at work (SCCs) are related to employees' well-being (i.e., state negative affect, NA) and nonwork experiences (i.e., psychological detachment from work and negative work reflection at home) on a daily level. Using experience-sampling methodology, we collected data from 98 civil service agents over 5 working days. Hierarchical linear modeling revealed that on the daily level, SCCs were related to employees' NA as well as with their nonwork experiences. Specifically, SCCs were negatively related to psychological detachment from work and positively related to negative work reflection after work. Furthermore, results provide support for the mediating role of NA in the SCC-nonwork experiences relationship. The findings of the present study broaden the scope of workplace conflict research by showing that conflicts are not only associated with employees' impaired well-being but even encroach on their nonwork experiences. © 2012 American Psychological Association.